Socio Cultural Diversity and Economic Development: Policy Implications for Southeast Asian Integration - Balbir Bhasin; Lee Keng Ng; James Beard; Cliff Scott (International Journal of Small and Medium Enterprises and Business Sustainability, 2018)
The ten countries of Southeast Asia have very diverse cultures, ranging from differences in language, religion, history, geography, political structure, social framework, and world view. How do these differences affect the ASEAN countries’ efforts at economic development, modernization, and regional integration? As they move towards unifying as an ASEAN Economic Community, this paper endeavors to assess options to meeting the challenges posed by socio-cultural integration. These include creating a common identity, individual and institutional empowerment, learning a common language, cultural education, and civic capacity building, and learning from the EU experience.